Factores biológicos psicológicos sociales y el consumo de alcohol en estudiantes de secundaria Iquitos Perú 2024 - Hidalgo Sairo, Cristian (2026)
The study titled Biological, Psychological, Social Factors and Alcohol Consumption in High School Students, Iquitos, Peru, 2024 aimed to determine the relationship between these factors and alcohol consumption in 793 students from 1st to 5th year of secondary education at the Educational Institution 60014 Santo Cristo de Bagazan. The research employed a quantitative, descriptive, correlational, non-experimental, cross-sectional design, using a self-administered questionnaire as the data collection technique. The results showed that most participants were in the 1st year (26.2%), male (55.5%), and in early adolescence (50.1%). Low levels of stress (50.1%) and high self-esteem (55.1%) predominated. Additionally, (64.4%) reported parental history of alcohol consumption, and (51.2%) came from nuclear families. Although (57.4%) did not consume alcohol, (42.6%) exhibited some level of consumption, with harmful consumption (16%) and hazardous consumption (14.8%) being the most notable. The analysis revealed significant associations between age (p<0.016), stress (p<0.001), self-esteem (p<0.005), parental history of alcohol use (p<0.001), and family type—particularly extended and single-parent families (p<0.001)—and alcohol consumption. In contrast, sex showed no significant relationship (p<0.080). It is concluded that these biopsychosocial factors influence alcohol consumption, highlighting the need to strengthen strategies that reduce risks and promote healthy lifestyles in adolescents.